Teaching Performance and Research According to the Students of the Doctorate in Educational Sciences at the UNE-Lima Graduate School, 2022 - Jesselle Roxana Rodas García (Migration Letters, 2023)
Teaching performance and research are two significant factors for achieving qualifying results from universities, requiring the reflection of the academic community in order to understand the interaction between these aspects. In this sense, the present study has been developed with the objective of determining the relationship that exists between teaching performance and research according to the students of the Doctorate in Educational Sciences at the UNE-Lima Graduate School, 2022. Likewise, this The research has a quantitative approach, basic type, correlational descriptive, with a non-experimental, cross-sectional design, with a hypothetical-deductive method. The sample was made up of 100 students of the Doctorate in Educational Sciences of the EPG of the UNE. The students were given two questionnaires structured through items with a Likert scale, duly validated by expert judgment and with a Cronbach’s Alpha reliability of 0.893 for the first instrument and 0.898 for the second instrument. The results were obtained using the Chi-square statistic and the gamma coefficient for ordinal variables, where at a reliability level of 95% and with a p-value = 0.000; That is, less than 0.05, it was evident that there is a significant relationship between both study variables, having obtained a gamma value of 0.870, determining that there is a high degree of association, being positive. It is concluded then that the better the teaching performance, the higher the level of research of the students.